Association between Socioeconomic Status and Motor Skill Development among Preschool Children of Lekhnath, Pokhara: A Cross-Sectional Study (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: Gross and fine motor skills are both necessary for healthy growth. According to studies, children from lower “Socioeconomic Status (SES)” families have delayed development of these fundamental motor skills, placing them at risk for delayed motor skill development. The current research’s objective was to study the occurrence of developmental risks and the variances between the gross as well as fine motor growth related to the SES of pre-schoolers in Pokhara.MATERIALS AND METHODS: One district preschool in the Lekhnath municipality of Pokhara was selected for the study. 102 elementary school students between 3-6 years were evaluated. Children’s fine and gross motor skill and SES of their parents were calibrated. The values were compared and evaluated for the various economic status and genders keeping p